Sustainable Travel for Wellbeing: Tourist Experiences in Chinese Destinations (International Journal of Social Research & Innovation, 2023)
Immersion in nature, culture and connection, physical and mental wellbeing are travel drivers which are intertwined with one another in wellness tourism. The purpose of this study was to explore and understand this phenomenon by analysing the positive health experiences of tourists in different types of naturebased wellness tourism destinations in China. Guided by grounded theory, and netnographic approach, this research used over 600,000 words of travelogue content on Mafengwo travel platform, for the past five years up to March 2023. A three-level coding approach was used to compare the impact of five different types of wellness tourism destinations on tourists’ health experiences. The results show that tourists’ mental health experiences are more notable in water-based destinations and traditional wellness culture destinations, while physical health experiences are more notable in forest, mountain, and hot spring destinations. The findings show that Chinese tourists highly value connection to nature as a source of holistic wellbeing, while wellbeing is further enhanced through availability of resources and activities targeted to meet physical, emotional, social, cognitive, and spiritual wellbeing of tourists. Suggestions are made to help enhance the health experience of tourists. The results are notable for constructing wellness tourism destinations in practice and provide theoretical references for future research on wellness tourism destinations.